Single-cell and isoform-specific translational profiling of the mouse brain - Samantha L. Sison; Federico Zampa; Eric R. Kofman; Su Yeun Choi; Pratibha Jagannatha; Grady G. Nguyen; Jack T. Naritomi; Asa Shin; Akanksha Khorgade; Wenhao Jin; Chun-Yuan Chen; David M. Sievert; et al. (Nature, 2026)
Abstract The brain displays the richest repertoire of post-transcriptional mechanisms regulating mRNA translation 1–11 . Among these, alternative splicing has been shown to drive cell-type specificity and, when disrupted, is strongly linked to neurological disorders 12–17 . However, genome-wide measurements of mRNA translation with isoform sensitivity at single-cell resolution have not been achieved. To address this, we deployed Surveying Ribosomal Targets by APOBEC-Mediated Profiling (Ribo-STAMP) coupled with short-read and long-read single-cell RNA sequencing in the brain 18 . We generated the first isoform-sensitive single-cell translatomes of the mouse hippocampus at postnatal day 25, discovering cell-type-specific translation of 3,857 alternative transcripts across 1,641 genes and identifying isoforms of the same genes undergoing differential translation within and across 8 different cell types. We defined high and low translational states in CA1 and CA3 neurons, with synaptic and metabolic genes enriched in high states. We found that CA3 exhibited higher basal translation compared with CA1, as confirmed by metabolic labelling of newly synthesized proteins and immunohistochemistry of translational machinery components. This accessible platform will expand our understanding of how cell-type-specific and isoform-specific translation drives brain physiology and disease.